Feasibility Study for Construction of Solar Grade Silicon Wafer Manufacturing Plant with Production Capacity of 2 GWp in Batam Industrial Area, Indonesia - Oetomo, Dedy Setyo; Amalia, Akhsani Nur (Yayasan Gema Bina Nusantara, 2025)
This study evaluates the technical and economic feasibility of establishing a 2 GWp solar-grade silicon wafer manufacturing facility in Batam Industrial Area, Indonesia. The proposed plant utilises Chinese-manufactured equipment for key processes, including 40 CZ Puller units, 20 Multi-Wire Saw units, and 15 CMP systems, with polysilicon as the primary raw material. A comprehensive analysis incorporating technical, financial, operational, and market aspects demonstrates project viability with an IRR of 18-20% and a payback period of 5-6 years. The total investment of USD 250 million encompasses equipment, infrastructure, and working capital. Results indicate favourable technical feasibility with established Chinese equipment manufacturers meeting international quality standards. Financial analysis shows strong potential returns, supported by growing regional solar panel demand and Batam's strategic advantages. Key risks identified include polysilicon price volatility, technological obsolescence, and market competition, with structured mitigation strategies proposed.